Respectful maternity care experiences of South Asian refugees in the US: a qualitative study - Smith, Denise C.; Thumm, E. Brie; Tien, Nai Chieh (Geri); Kissler, Katherine (Frontiers in Public Health, 2025)
IntroductionImmigrants and refugees giving birth in the United States face challenges in receiving high-quality maternity care. The purpose of this study was to understand the experiences of recent refugees from ethnic communities displaced from southern Asia and resettled in the United States.Materials and methodsThe qualitative study used focus group discussions with three refugee communities who have given birth since resettlement in the United States. Using thematic analysis, we applied the concepts of respectful maternity care to identify themes.ResultsFive themes emerged from the analysis: (1) interpersonal caring, (2) flaws in US maternity care are amplified for refugees, (3) multidimensionality effects knowledge, preferences, and expectations, (4) complexity of the US health system combined with unfamiliarity contributes to lack of confidence, and (5) problems with language interpretation.DiscussionThe identified themes can inform specific, actionable policies and programs that improve care for immigrant and refugee communities including investment in nursing care, implementation of multilingual doula care, improvements in language services, and robust childbirth education.